การพัฒนาบทเรียนบนเครือข่ายอินเทอร์เน็ตตามแนวทฤษฎีคอนสตรัคติวิสต์ - อำพลพงษ์, อมรินทร์ (Journal of Education Studies, Chulalongkorn University, 2019)
This research aims to study, assess, and develop online IT lessons involved with Constructivist Theory to boost learners’ confidence, ability and attitude in design technology. In the academic year 2/2015, two Grade 4 classes: Mattayom 4/3 (Science-Maths-programme students) and Mattayom 4/7 (Language-Social-Science-programme students) of Chulalongkorn University Demonstration Secondary School were targeted due to the different study programs and mixed abilities in computers and IT. Three instruments were applied to this research consisting of online lessons used Constructivist Theory, pre- and post-tests, along with attitude tests. The online lessons aim to make standardised IT lessons owing to their validity, degrees of difficulty, variance, and reliability of contents. If students reach 75 percent, they meet the requirements. Pre- and post-tests are utilized to assess students’ performances before and after the lessons. An attitude test is applied to measure student satisfactionand viewpoints on the online lessons. The average number of students’ test results (x̅) and standard deviation (S.D.) were used for analysis and as tools in the case study. The results represent the effectiveness of the above-mentioned online lessons for both Science-Math and Language & Social Science classes to supplement their IT studies. Apparently, study programs will not make a lot of difference in the tests even though the Science-Maths programmestudents met the higher efficiency of 85.30/86.7 while the Language-Social Science programmestudents’ performances were 76.68/76.09. In summary, both groups were at least 75 percent, which is satisfactory, i.e. 3.5. In other words, it is equal to Level 5 (Well-qualified in school IT lessons) according to the Likert scale.